The Influence Of Cultural, Social And Personal Factors On The Interest In Purchase Intention Non-Subsidized Fertilizer At Toko UD. Sejahtera Bersama In Kecamatan Bahorok - Rendi Dinova; Annisa Febrina (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
Fertilizer is a substance or material that is used in plants to improve physical, chemical, or biological characteristics in order to increase the availability of nutrients, which results in an increase in plant growth. There are two types of fertilizer in Indonesia: subsidies and non-subsidized. While subsidies are provided by the government, non-subsidized are those that are provided outside of government programs and do not qualify for subsidies. Non-subsidized fertilizers, although they have superior quality and technology compared to subsidized fertilizers, still face problems in terms of farmers' Purchase Intention, especially in Kecamatan Bahorok. The purpose of this study is to examine the effects of cultural, social, and private factors on the desire to purchase intention non-subsidized fertilizer at Toko UD. Sejahtera Bersama in Kecamatan Bahorok. Data collection using a questionnaire given to 90 respondents. The model used is multiple linear regression and is processed using SPSS. The results of this study indicate that cultural factors partially do not have a positive and significant influence, social factors partially do not have a positive and significant influence and personal factors partially have a positive and significant influence. The Adjusted R Square value of 0.541 means that Purchase Intention can be explained by cultural, social and personal factors by 52.5% and the remaining 47.5% can be explained by other variables not studied.